2017
DOI: 10.5798/dicletip.298579
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Serum Levels of Selenium, Zinc, and Copper in Adolescents with Idiopathic Scoliosis

Abstract: Objective: The purpose of this study was to investigate the serum levels of selenium, zinc and copper on the etiology of idiopathic scoliosis in adolescents. Methods: Forty four idiopathic scoliosis patients between 10 and 17 years of age were considered in this study. The vertebra curvature degrees of the patients were between 28° and 82°. The idiopathic scoliosis patients were assigned to two groups based on their vertebra curvature degrees. Curvature degree of 45° and lower was labeled as group 1 and curvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It is speculated that abnormal osteogenic function promotes the occurrence and development of scoliosis [11] . As for sh, shrimp and egg, previous studies have shown that the serum selenium content of children with scoliosis is signi cantly lower than that of healthy children of the same age, and it is negatively correlated with Cobb's angle [12] . Some scholars speculate that selenium is related to connective tissue collagen synthesis, which reduces the stability of muscle ber tissue and nally leads to scoliosis [13] .…”
Section: The Relationship Between Living Habits and Ieosmentioning
confidence: 99%
“…It is speculated that abnormal osteogenic function promotes the occurrence and development of scoliosis [11] . As for sh, shrimp and egg, previous studies have shown that the serum selenium content of children with scoliosis is signi cantly lower than that of healthy children of the same age, and it is negatively correlated with Cobb's angle [12] . Some scholars speculate that selenium is related to connective tissue collagen synthesis, which reduces the stability of muscle ber tissue and nally leads to scoliosis [13] .…”
Section: The Relationship Between Living Habits and Ieosmentioning
confidence: 99%